PHYSICAL FITNESS (SKJ) TRAINING FOR CHILDREN AT TITI PANJANG NEGERI PRIMARY SCHOOL - Fakhrur Rizal; Melfa Br Nababan; Afrizal (CV. Naskah Aceh, 2023)
The aim of this community service is to promote Student Physical Fitness Gymnastics (SKJ) and produce Student SKJ instructors who have talent in the field of gymnastics. Apart from that, this community service is also carried out to empower the community, especially students at Titi Panjang Public Elementary School, Leuser District, by creating a routine for implementing Student SKJ on an ongoing basis which aims to increase the fitness of students, especially at Titi Panjang Public Elementary School, Leuser District. The target of this activity is Titi Panjang State Elementary School, Leuser District. The method used is training consisting of theory, discussion, training followed by practice/practice both individually, in groups and as a whole. The time required for this activity is 24 meetings over 2 months. The results of the SKJ Student Gymnastics training were that students at SD Negeri Titi Panjang, Leuser District who took part in this training activity were able to practice the SKJ Student movements and how to make the body healthy and fit by doing all the SKJ Student movements and they were able to repeat the exercises taught. The results obtained after carrying out this training were 82% of students at SD Negeri Titi Panjang, Leuser District, specifically grades 4, 5 and 6, who were able and willing to implement the Student SKJ as a routine activity twice a week at school. From the SKJ Student physical activity, it shows that there has been an increase in knowledge related to the physical activity of the SKJ Student Gymnastics movements. Related training has an impact on improving healthy and fit lifestyles.